1999
DOI: 10.1006/viro.1999.9674
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Human Sera Reactivities in Immunoblots with Recombinant Human Herpesvirus (HHV)-8 Proteins Associated with the Latent (ORF73) and Lytic (ORFs 65, K8.1A, and K8.1B) Replicative Cycles and in Immunofluorescence Assays with HHV-8-Infected BCBL-1 Cells

Abstract: The development of reliable, sensitive, and specific serological methods for the detection of human herpesvirus-8 (HHV-8) antibodies is critical for a thorough understanding of HHV-8 prevalence and pathogenesis. To evaluate the potential usefulness of HHV-8 proteins in measuring the responses against both latent and lytic antigens, we selected 1 latent [open reading frame (ORF) 73] antigen and 3 HHV-8 lytic antigens (ORFs 65, K8.1A, and K8.1B) previously identified as immunogenic [Virology (1998) 243, 208-217]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
54
3
5

Year Published

2000
2000
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 25 publications
6
54
3
5
Order By: Relevance
“…The genesis of KSHV seroepidemiology came from studies employing easily cultured, uniformly KSHV-infected B-lymphoma cell lines (PEL cell lines) as the source of viral latent antigen (176,250,355). PELs have since served as the primary target for indirect immunofluorescent-antibody (IFA) approaches to measure levels of antibody to both latent and lytic KSHV proteins in clinical serum samples and have been successfully used as a source of protein extract in confirmatory immunoblots (93,175,176,250,290,343,355,474,545). When clinical sera are incubated with latently infected PEL cells or nuclei, they are scored positive for previous viral exposure if a characteristic punctate nuclear stain is observed (176,250,355).…”
Section: Clinical Detection Of Kshv and Estimates Of Infection In Thmentioning
confidence: 99%
“…The genesis of KSHV seroepidemiology came from studies employing easily cultured, uniformly KSHV-infected B-lymphoma cell lines (PEL cell lines) as the source of viral latent antigen (176,250,355). PELs have since served as the primary target for indirect immunofluorescent-antibody (IFA) approaches to measure levels of antibody to both latent and lytic KSHV proteins in clinical serum samples and have been successfully used as a source of protein extract in confirmatory immunoblots (93,175,176,250,290,343,355,474,545). When clinical sera are incubated with latently infected PEL cells or nuclei, they are scored positive for previous viral exposure if a characteristic punctate nuclear stain is observed (176,250,355).…”
Section: Clinical Detection Of Kshv and Estimates Of Infection In Thmentioning
confidence: 99%
“…It has been shown that the transmembrane glycoprotein K8.1 is part of the viral envelope (27). K8.1 is highly immunogenic in the natural host (40) and is frequently used in HHV-8 serologic assays (26,49,60). The physiological function of K8.1 or the other rhadinoviral glycoproteins encoded at comparable genomic positions has not been identified so far.…”
mentioning
confidence: 99%
“…The cDNAs encoding ORF65 and ORF73 were previously identified by screening a cDNA library from TPA-induced BCBL-1 cells with serum from a patient positive for human immunodeficiency virus and KSHV (1,30). They were then expressed as a glutathione S-transferase (GST) fusion protein in a baculovirus system, purified, and injected into rabbits.…”
Section: Methodsmentioning
confidence: 99%